"It Just Never Worked Out": How Transgender and Gender Expansive Youth Understand their Pathways into Homelessness. Issue 4 (October 2017) - Shelton, Jama; Bond, Lynden
Many transgender and gender-expansive young people live outside of mainstream society, due to structural barriers that limit access to employment, health care, education, and public accommodations, as well as prejudice and discrimination within their families and communities. These structural barriers can be understood as cisgenderism. Though a growing body of research examines lesbian, gay, bisexual, and transgender (LGBT) youth homelessness, gaps in knowledge about the specific experiences of transgender and gender-expansive homeless youth remain. This phenomenological qualitative investigation explored aspects of transgender and gender-expansive youth's experiences related to homelessness. This article focuses on participants' understanding of their pathways into homelessness.